PELAKSANAAN UPACARA MEMATUA DAN MANDIU PASILI DALAM PERKAWINAN ADAT SUKU KAILI (Suatu Tinjauan Hukum Islam dan Hukum Adat) - Raden, Sahran (Hunafa: Jurnal Studia Islamika, 2011)
In essence, marriage is one of the things desired by everyone, male or female, in their lives. It is also seen as a change of status in a person from living in single life into family one through the media dealing with this. In terms of kinship, the relationship between society and family can occur through marriage and mate selection in order that a new family is established. This is an event in peopleâs life which is considered important and sacred in their lives. For ethnic group of Kaili, marriage will give a meaning in communityâs life, which is represented in the phrases of Kalinese language, such as, among others, momboli tanda tuvu (leaving consecrated life).